Jet lag effects on lower-limb hemorheological and venous hemodynamics rates in athletes - Safonov, L. V. (Theory and Practice of Physical Culture, 2017)
The study of the hemorheological and bio-impedance rates in athletes specializing in speed-strength and cyclic sports diagnosed with venous circulation deficiency in the lower limbs and those free of vascular pathologies has not revealed any statistical significant differences in the study rates, which, in view of the absence of the clear clinical picture and available methods of screening diagnostics, results in the underestimation of the importance of diagnosing of venous circulation deficiency in the lower limbs in elite athletes. Negative variations of the lower-limb hemorheological and bio-impedance rates directly correlate with the flight time and have no correlation with the degree of venous circulation deficiency in the lower limbs, lasting in both the athletes diagnosed with the disorders of venous blood circulation in the lower limbs and those free of vascular pathologies. The flights up to 4 hours long did not cause any meaningful health impairments in the athletes from the studied sports, but the athletes diagnosed with functional or chronic lower-limb venous blood circulation disorders were found to have more expressed negative variations of the study rates. With the increase of the flight time lasting longer than 4 hours negative variation of the study rates correlated with the flight time, moreover, the detected variations were more expressed in the athletes diagnosed with functional or chronic lower-limb venous blood circulation disorders. The study finding urges a set of reasonable therapeutic and preventive actions be taken to counter de-compensations of venous blood circulation in the lower limbs.